Blockchain Network Based Hyperledger Fabric Techniques – A Survey - Ayyasamy, S. (Journal of Ubiquitous Computing and Communication Technologies, 2023)
Blockchain is described as a cacheable, immutable that makes tracking transactions and assets in a corporate network easier. Hyperledger is a free software initiative that was designed to aid in the development of distributed ledgers based on blockchain technology. Hyperledger has several frameworks, including Hyperledger Fabric, Hyperledger Burrow, Hyperledger Indy, Hyperledger Sawtooth, and Hyperledger Grid. There are also other Hyperledger-based technologies used in blockchain. This research paper investigates the many applications and strategies employed by the Hyperledger Fabric blockchain network. There will also be a discussion regarding Hyperledger frameworks, future improvements, and overall applications used.
Keywords: Network security; fabric technology; hyperledger networks; transaction management; cryptographic